Prevalence and risk factors of Cryptosporidium spp. on dairy farms in Bogor - Arifin Budiman Nugraha; Umi Cahyaningsih; Etih Sudarnika (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2021)
Cryptosporidial infection is one of the most common causes of diarrhea in humans and livestock worldwide. This study was conducted to estimate the prevalence of Cryptosporidium infection and to identify potential risk factors associated with shedding of oocysts in Bogor. A total of 308 faecal samples were collected from 136 calves less than 6 months, 44 from those 6-12 months and 128 from those than 12 months. Data of factors potentially associated with the likelihood of Cryptosporidium spp. infection were recorded (i.e., enviromental status, size of herd, and herd management). Cryptosporidium spp. oocyst was identified by using modified acid fast (Ziehl Neelsen) staining technique and microscopically examined under 400x magnifition. Results showed that the prevalence of cryptosporidiosis in Bogor was 21.1% (CI 95%; 16.5%-25.6%). The highest prevalence was 29% (CI 95%; 26.8%-31.7%) in cattle aged less than 6 months. The oocysts abundance were around <5 oocysts per microscopy visual area. Data was analyzed using logistic regression models. Statistical analysis showed that there were association between cryptosporidiosis and calves aged less than 6 months with an odds ratio (OR) of 2.7 (CI 95%; 1.5-5.2) times compared with cattle aged more than 12 months.